Comprehensive Review on a Complicated Endocrine Disorder (Acromegaly) - Sanjita Das; . Divya (Current Practice in Medical Science Vol. 9, 2022)
The purpose of this article is to make people familiar with signs and symptoms as well as treatment of acromegaly. Acromegaly is a disease or ailment that results in excessive bodily tissue growth and the malfunction of other metabolic processes. It is brought on by the hypersecretion of growth hormone from the anterior pituitary. Middle-aged persons are most commonly affected by acromegaly, which is typically brought on by a benign (non-cancerous) tumor. Patients with acromegaly have pain in the joints, physical deformities, deepening of voice, bulging chest, protruding lower jaw, large feet and hands, oily skin, vision disorder or erectile dysfunction (impotence). Acromegaly occurs after the fusion of growth plates while gigantism occurs before the fusion of growth plates. It is concluded that any disease management strategy must focus on the needs of patients and do everything possible to improve patients’ healthcare experience and minimize their treatment burden. The present study may be helpful for a systematic and targeted research for more convenient management of acromegaly.